Simulation of influence of perturbation parameters on the new dual-channel capacitive mems gravimeter performance - Bezvesilna, Olena; Khylchenko, Tetiana; Tkachuk, Andriy; Nechai, Sergii (Eastern-European Journal of Enterprise Technologies, 2016)
The paper considers a new dual-channel capacitive MEMS gravimeter of the automated aviation gravimetric system whose accuracy exceeds that of gravimeters that exist at present. It describes in detail its design, which consists of two identical channels. Each of them contains capacitive elements. The connection in series of the adder, amplifier, digital module and OC is performed by means of shielded coaxial cables. All this provides for an increased accuracy in measuring the anomalies of the acceleration of gravity and eliminates the impact of error from vertical acceleration. The simulation of the suspension with complex shape was carried out: the magnitude of impact amounted to 10 µN, displacement of the end of the elastic element equaled 0.5 µm. Based on this refinement, it is possible to accurately determine the value of coefficient of elasticity of the folded suspension. The system was tested on stability by the Nyquist and Hurwitz criteria. Using PC, a change in the initial signal was examined for different values of perturbation amplitudes and frequency for the most unfavorable resonance cases of a dual-channel capacitive gravimeter. An analysis of data revealed that an increase in amplitudes of horizontal acceleration does not affect the amplitude of the forced DCG oscillations. Thus, the aviation gravimetric system proposed provides for a significant increase in accuracy of measuring the anomalies in the acceleration of gravity, and is appropriate for implementation.